The Relationship between Adolescent Self-Control and Casual Sexual Behavior - Khansa Afifah Indri Amelia; Veny Elita; Yesi Hasneli N (Journal of Education Technology Information Social Sciences and Health, 2024)
Introduction: Currently, teenagers have a permissive attitude towards unrestricted sexual behavior, this is due to the possibility of dating which facilitates this behavior, so good self-control is needed to prevent promiscuous sexual behavior. This study aims to determine the relationship between adolescent self-control and casual sexual behavior at SMKN 6 Pekanbaru. Method: This research uses a descriptive correlation design with a cross sectional approach. The research sample was 100 respondents taken based on inclusion criteria using probability sampling techniques with a simple random sampling method. This research uses a Likert questionnaire which is valid and reliable. The analysis used is univariate and bivariate analysis using the chi-square test. Results: The majority of respondents had high self-control as many as 58 respondents (58.0%) and high levels of promiscuous sexual behavior as many as 63 respondents (63.0%). The results of statistical tests show that there is no relationship between adolescent self-control and casual sexual behavior with p value (0.987) alpha (0.05). Conclusion: Adolescent self-control does not have a significant relationship with casual sexual behavior. Recommendation: Education and evaluation is needed for students at SMKN 6 Pekanbaru about the negative impacts that can occur if they do not control themselves towards promiscuous sexual behavior.